Association of tenofovir disoproxil fumarate exposure with chronic kidney disease and osteoporotic fracture in US veterans with HIV. (2nd October 2020) - Sutton, S. Scott; Magagnoli, Joseph; Hardin, James W.; Hsu, Ling-I; Beaubrun, Anne; Majethia, Sunil; Cummings, Tammy H.
Abstract: Background: Tenofovir disoproxil fumarate (TDF)-based regimens have been associated with impaired kidney function and loss of bone mineral density among patients living with HIV (PLWH). We assess the association between TDF exposure and the odds of chronic kidney disease (CKD) and osteoporotic fracture in HIV patients. Methods: Demographics, administrative claims, and pharmacy dispensation were extracted from the Veterans Affairs Informatics and Computing Infrastructure (VINCI). Patients were categorized based on TDF utilization. Incidence rates for patients exposed and unexposed to TDF were calculated per 1000 patient-years (PYs). Logistic regression was used to calculate the odds of outcome after adjusting for baseline and clinical characteristics. Results: The sample included 4, 630 PLWH who were currently exposed to TDF and 1, 181 who were never exposed to TDF for the CKD analyses. For fracture analyses, the sample included 6, 883 PLWH who were currently exposed to TDF and 1, 951 who were never exposed to TDF. In adjusted models, current TDF exposure was associated with increased odds of CKD compared to never having been exposed (OR: 1.48, 95% CI: 1.18–1.85). Odds of fracture were 2.32 times higher for patients who were currently on a TDF regimen (OR: 2.32, 95% CI: 1.58–3.42) compared to those who had never been exposed to TDF in adjusted models. Conclusions: In a large cohort of US veterans with HIV, current exposure to TDF was associated with a 48% higher odds of CKD and a greater than two-fold increase in the odds of osteoporotic fracture.